2011
DOI: 10.4049/jimmunol.1003631
|View full text |Cite
|
Sign up to set email alerts
|

Bruton’s Tyrosine Kinase Is Required for TLR-Dependent Heme Oxygenase-1 Gene Activation via Nrf2 in Macrophages

Abstract: Heme oxygenase (HO)-1 is the inducible isoform of the rate-limiting enzyme of heme degradation and provides cytoprotection against oxidative stress by its products carbon monoxide and biliverdin. More recently, HO-1 has also been shown to exert immunomodulatory functions via cell type-specific anti-inflammatory effects in myeloid/macrophage cells. In the current study, it is demonstrated that Bruton's tyrosine kinase (Btk), the gene of which is mutated in the human immunodeficiency X-linked agammaglobulinemia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 64 publications
6
50
0
Order By: Relevance
“…30,93 More recent studies show that bone marrow-derived Mø or rMoPh display biphasic expression of proinflammatory factors followed by anti-inflammatory and reparative factors in response to challenge with lipopolysaccharide or ischemic injury, respectively. 62,92,94,95 Within the kidney, specific paracrine factors released from renal parenchymal cells, such as IL-10, DAMPs, or apoptotic bodies, initiate or augment this phenotypic reprogramming of rMoPh. 90,96,97 Figure 2.…”
Section: Plasticity Of Function Of Rmoph During Renal Injury and Repairmentioning
confidence: 99%
“…30,93 More recent studies show that bone marrow-derived Mø or rMoPh display biphasic expression of proinflammatory factors followed by anti-inflammatory and reparative factors in response to challenge with lipopolysaccharide or ischemic injury, respectively. 62,92,94,95 Within the kidney, specific paracrine factors released from renal parenchymal cells, such as IL-10, DAMPs, or apoptotic bodies, initiate or augment this phenotypic reprogramming of rMoPh. 90,96,97 Figure 2.…”
Section: Plasticity Of Function Of Rmoph During Renal Injury and Repairmentioning
confidence: 99%
“…Indeed, Btk has been shown to be an important regulator for the activity of several transcription factors including NF-кB, STAT5, FOXO1, Nrf2 and BRIGHT 42,[60][61][62][63] . Notably, Btk contains an NLS-like sequence in the PH domain, but it has been shown to be functionally inactive 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that Btk regulates the expression level of Nrf2 gene 42 . To examine the effect of Btk on Nrf2/HO-1 expression in response to PRIMA-1 exposure, we probed the membranes with both Nrf2 and HO-1 antibodies.…”
Section: Prima-1 Downregulates Btk Expressionmentioning
confidence: 99%
“…In the context of phagocytosis, TLR stimulation has been shown to differentially affect the uptake and cross-presentation of cellular Ags by monocyte-derived dendritic cells (20). Although Btk has been shown to be involved in TLR7 mediated responses in myeloid cells (11), the effect of loss of Btk on TLR7-induced changes to myeloid cells has not yet been fully explored.…”
mentioning
confidence: 99%
“…Recent studies, however, have focused on its role in regulating innate immune responses in myeloid cells, acting downstream of TLR4 and the antiviral TLRs, TLR3, -7, and -9, to regulate proinflammatory cytokine and type I IFN production (6)(7)(8)(9)(10)(11). Btk has also been shown to interact with and become activated following ligation of TLR8 and -9 in the monocytic cell line THP-1 (8).…”
mentioning
confidence: 99%